Westonci.ca is the best place to get answers to your questions, provided by a community of experienced and knowledgeable experts. Discover solutions to your questions from experienced professionals across multiple fields on our comprehensive Q&A platform. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
Answer:
[tex]\boxed{ \sf x=\dfrac{4\pm\sqrt{43}}{2}}[/tex]
Explanation:
[tex]\rightarrow \sf \dfrac{1}{x-5}+\dfrac{3}{x+2}=4[/tex]
make the denominators same
[tex]\rightarrow \sf \dfrac{1(x+2)}{(x-5)(x+2)}+\dfrac{3(x-5)}{(x+2)(x-5)}=4[/tex]
join the fractions together
[tex]\rightarrow \sf \dfrac{x+2+3x-15}{(x-5)(x+2)}=4[/tex]
cross multiply
[tex]\rightarrow \sf x+2+3x-15=4(x-5)(x+2)[/tex]
simplify
[tex]\rightarrow \sf 4x-13=4x^2-12x-40[/tex]
group the variables
[tex]\rightarrow \sf 4x^2-16x-27 = 0[/tex]
use quadratic formula
[tex]\rightarrow \sf x = \dfrac{-\left(-16\right)\pm \sqrt{\left(-16\right)^2-4\cdot \:4\left(-27\right)}}{2\cdot \:4}[/tex]
simplify the following
[tex]\rightarrow \sf x=\dfrac{4\pm\sqrt{43}}{2}[/tex]
Answer:
[tex]x=\dfrac{4 \pm \sqrt{43}}{2}[/tex]
Step-by-step explanation:
Given equation:
[tex]\dfrac{1}{(x-5)}+\dfrac{3}{(x+2)}=4[/tex]
Make the denominators of the algebraic fractions the same, then combine them into one fraction:
[tex]\begin{aligned}\implies \dfrac{1}{(x-5)} \cdot \dfrac{(x+2)}{(x+2)}+\dfrac{3}{(x+2)}\cdot \dfrac{(x-5)}{(x-5)} & =4\\\\\implies \dfrac{x+2}{(x-5)(x+2)}+\dfrac{3(x-5)}{(x-5)(x+2)} & = 4\\\\ \implies \dfrac{x+2+3(x-5)}{(x-5)(x+2)} & = 4\\\\ \implies \dfrac{4x-13}{(x-5)(x+2)} & = 4 \end{aligned}[/tex]
Multiply both sides of the equation by [tex](x-5)(x+2)[/tex]:
[tex]\begin{aligned}\implies \dfrac{(4x-13)}{(x-5)(x+2)}\cdot (x-5)(x+2) & = 4(x-5)(x+2)\\\\\dfrac{(4x-13)(x-5)(x+2)}{(x-5)(x+2)} & = 4(x-5)(x+2)\\\\4x-13 & = 4(x-5)(x+2)\\\\4x-13 & =4x^2-12x-40\\\\4x^2-16x-27 & = 0\end{aligned}[/tex]
Solve using the Quadratic Formula:
[tex]x=\dfrac{-b \pm \sqrt{b^2-4ac} }{2a}\quad\textsf{when}\:ax^2+bx+c=0[/tex]
[tex]\implies a=4\\\implies b=-16\\\implies c=-27[/tex]
Therefore:
[tex]\implies x=\dfrac{-(-16) \pm \sqrt{(-16)^2-4(4)(-27)} }{2(4)}[/tex]
[tex]\implies x=\dfrac{16 \pm \sqrt{688}}{8}[/tex]
[tex]\implies x=\dfrac{16 \pm 4 \sqrt{43}}{8}[/tex]
[tex]\implies x=\dfrac{4 \pm \sqrt{43}}{2}[/tex]
We hope this was helpful. Please come back whenever you need more information or answers to your queries. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.